Minority writing: The case of Friuli-Venezia Giulia (Italy), Goriška and Coastal-Karst regions (Slovenia) - Toroš, Ana (Slavia Centralis, 2020)
The paper discusses the literature of national and linguistic minorities along the Slovene-Italian border area (Slovene and Friulian literature in Italy, Italian literature in Slovene Istria), comprised of the Friuli-Venezia Giulia region in Italy, and the Goriška and Coastal-Karst regions in neighbouring Slovenia. The paper claims that a new methodological approach is needed to study these literatures, namely one that will upgrade previous research (studying the literature’s regional specifics which stem from the authors’ common living environment, regardless of their linguistic and national identity, and the depiction of foreign culture in minority literature) and move towards regional comparative literature. Results of such studies would be useful to bolster the teaching materials in literature classes in the area concerned.